Facteurs d’influence des choix résidentiels en zone inondable dans le cinquième arrondissement communal de Niamey - Adam Abdou Alou (EchoGéo, 2021)
This study focuses on the factors influencing residential choices that determine at least in part the individual level of risk exposure of flood in the neighborhoods of the fifth municipality of Niamey city. Based on a qualitative survey of real estate professionals, risk managers, local elected officials and residents, the study highlighted socio-economic factors and the reasons why residents choose to live in a flood area while being exposed to following extreme rainfall and hydrological events.